2019
DOI: 10.1186/s12879-019-4081-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics, clinical manifestations and laboratory findings in 850 patients with brucellosis in Heilongjiang Province, China

Abstract: Background Brucellosis has extensive clinical spectrum, clinicians have insufficient understanding of the disease, and the misdiagnosis rate is still high. By collecting and analyzing the clinical characteristics of patients with brucellosis in Heilongjiang Province to provide guidance and reference for clinicians to make timely diagnosis and treatment. Methods The demographic and epidemiological characteristics, clinical features, complications, laboratory findings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 23 publications
(36 reference statements)
5
46
3
2
Order By: Relevance
“…25 Of all the cases recorded the clinical manifestations, it was found that the most frequent symptoms were fatigue, hyperhidrosis, fever, arthralgia/myalgia, which is similar to most previous studies. [26][27][28][29] It was found that patients aged more than 60 years were more likely to had arthralgia/ myalgia than other age groups, and patients who had enlarged spleen in male were more than female; and in another study about clinical characteristics of brucellosis in different age groups, 30 it was reported that patients aged under 3 years old constituted the largest proportion (19.1%) of hepatosplenomegaly. In this study, most patients were diagnosed with acute brucellosis, and there was no statistically significant difference in clinical diagnosis between different age groups and genders, which was different from another study that reporting most (87%) patients under 15 years-old presented as acute cases.…”
Section: Discussionmentioning
confidence: 99%
“…25 Of all the cases recorded the clinical manifestations, it was found that the most frequent symptoms were fatigue, hyperhidrosis, fever, arthralgia/myalgia, which is similar to most previous studies. [26][27][28][29] It was found that patients aged more than 60 years were more likely to had arthralgia/ myalgia than other age groups, and patients who had enlarged spleen in male were more than female; and in another study about clinical characteristics of brucellosis in different age groups, 30 it was reported that patients aged under 3 years old constituted the largest proportion (19.1%) of hepatosplenomegaly. In this study, most patients were diagnosed with acute brucellosis, and there was no statistically significant difference in clinical diagnosis between different age groups and genders, which was different from another study that reporting most (87%) patients under 15 years-old presented as acute cases.…”
Section: Discussionmentioning
confidence: 99%
“…Brucella bacterial growth in blood culture was achieved in 22 of 70 cases. Typing was possible for only 18 isolates; 14 of them were brucella melitensis and 4 were brucella abortus.The clinical and laboratory features of the patients are presented in Tables 1 and 2. The treatment regimens were a 6-week combination of oral doxycycline+rifampicin, 6 weeks of doxycycline + 21 days of streptomycin or 7 days gentamicin, 6 weeks of doxycycline+trimethoprim-sulfamethoxazole, 6 weeks of rifampicin+trimethoprim-sulfamethoxazole, 6 weeks of doxycycline + ciprofloxacin, 6 weeks of rifampicin+ ceftriaxone. Aminoglycoside combination was used mostly in osteoarticulear involvement and ceftriaxone combination was used in pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Its broad spectrum of clinical presentations leads to delay in diagnosis and treatment. 6 The purpose of our study is to analyse the epidemiological, clinical, and laboratory findings and therapeutic features of our patients with brucellosis and compare our results with other similar studies in the literature.…”
Section: Introductionmentioning
confidence: 90%
“…As with complex clinical complications [17] , multiple organ damage can be caused by brucellosis,such as Brucellosis spondylitis.The incidence of meningitis and ion disorder (hyponatremia, hypokalemia and hypocalcemia) in hypocalcemia group was higher than that in normal corrected calcium group, indicating that hypocalcemia affected the occurrence of various systemic diseases, including blood system, nervous system, etc. [18] , suggesting that hypocalcemia may be associated with systemic disease in brucella patients.It has been described that CKD can cause nervous system complications through metabolic disorders (such as acidosis, hypocalcemia, hyperphosphatemia) [19] . Moreover, associated with the recurrence of hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%